A STUDY ON THE REASONS OF FAILING IN ACCOUNTING COURSE AND THE TEACHING TECHNICS FOR LEARNING ACCOUNTING BETTER - Kutluk, Filiz Angay; Dönmez, Adnan; Çavuşoğlu, Kürşad (International Journal of Research -GRANTHAALAYAH, 2018)
Competition is a force to the organizations to generate and apply new strategies to challenge the changing environment. Qualified labour force is also an important constituent in this way. Universities are also in competition to train successful, dynamic, qualified and innovative students who will be the future labour force. Updating the curriculum, searching more understandable teaching techniques and getting feedback from students and lecturers are some ways to be improved and preferable for universities. Each course may require different teaching techniques to be understood. The aim of this study is to investigate the reasons why the students fail in accounting courses and which teaching techniques may help them to understand accounting better. A survey is prepared and applied to the Summer school students who had “Accounting” related lessons in a university to detect the reasons they chose the course in summer school, the reasons that they failed in accounting course during the semester and the teaching techniques that they will better understand the course. The main reasons to fail Accounting lessons were that they didn’t study enough and they can’t understand accounting. The best method of understanding theoretical part of “Accounting” courses is using blackboard and power-point presentation together; for understanding practical/exercise part of is using blackboard. Most of the students have chosen Summer School to pass the failed courses.